Pengaruh Kegiatan Kokurikuler Terhadap Penguatan Karakter Integritas Peserta Didik Kelas XI SMAN 1 Tulang Bawang Tengah Tahun Pelajaran 2018/2019 - Desi Safitri; Berchah Pitoewas; Edi Siswanto (FKIP Unila, 2019)
The purpose of this research was to find out the influence of the co-curricular activities of the character strengthening of the eleventh grade students’ integrity at SMAN 1 Tulang Bawang Tengah academic year 2018/2019. The research method used was a quantitative descriptive method with a student research subject eleventh grade 35 respondents. In collecting the data, the researcher used polls and documentation. Based on the results of the study, it is known that giving co-curricular assignments can help learners understand the learning materials and reinforce the students' integrity character especially in honesty and responsibility. The results of this study showed that the students with the process of co-curricular activities are very influential with a percentage of 3 respondents (9%) considered as less influential category. There are 10 respondents (20%) considered as quite influential and 22 respondents (62%) are considered as a well-influential category. In the character strengthening integrity, there were 2 respondents (6%) considered as less influential category. There are 16 respondents (45%) in the category was influential and 17 respondents (49%) are in a well-influential category. The result of the study showed that 0.78 the influence of the co-curricular activities of the character strengthening of students ' integrity of XI SMAN Class 1 of the Central onion Bones can be categorized strongly.Tujuan penelitian ini untuk mengetahui pengaruh kegiatan kokurikuler terhadap penguatan karakter integritas peserta didik kelas XI SMAN 1Tulang Bawang Tengah tahun pelajaran 2018/2019. Metode penelitian yang digunakan metode deskriptif kuantitatif dengan subjek penelitian peserta didik kelas XI yang berjumlah 35 orang responden. Hasil penelitian ini menunjukkan bahwa peserta didik kelas XI SMAN 1 Tulang Bawang Tengah Tahun Pelajaran 2018/2019 dengan proses kegiatan kokurikuler sangat berpengaruh, dengan persentase sebanyak 3 responden (9%) termasuk kedalam kategori kurang berpengaruh. Sedangkan sebanyak 10 responden (20%) termasuk dalam kategori cukup berpengaruh dan sebanyak 22 responden (62%) dalam kategori berpengaruh dengan baik. Pada penguatan karakter integritas terdapat sebanyak 2 responden (6%) termasuk dalam kategori kurang berpengaruh. Sedangkan sebanyak 16 responden (45%) dalam kategori cukup berpengaruh dan sebanyak 17 responden (49%) dalam kategori berpengaruh dengan baik. Kata kunci: kegiatan, kokurikuler, integritas